Profile of final report FRGS/RAGS/ERGS/PRGS - Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina (2018)
In Malaysia, the authorities responsible for regulating consumer credit depend on the type of credit providers and the nature of the transactions involved. Credit providers can be generally divided into two namely bank and non-bank institutions. Banks are regulated by the Central Bank of Malaysia or Bank Negara Malaysia (BNM) by virtue of the Central Bank of Malaysia Act 2009 (Act 701)(CBA) and the Financial Services Act 2013 (Act 758)(FSA). In respect of non-bank credit providers, moneylenders and pawnbrokers are under the responsibility of the Ministry of Urban Wellbeing, Housing and Local Government (MUWHLG) as stipulated in the Moneylenders Act 1951 (Act 400)(MLA) and the Pawnbrokers Act 1972 (Act 81)(PBA) respectively. Both bank and non-bank credit providers offering hire-purchase facility are under the purview of the Ministry of Domestic Trade and Consumer Affairs (MDTCA) pursuant to the Hire-Purchase Act 1967 (Act 212)(HPA). All three regulators roles and functions are not specifically consumer protection. The roles of the central bank are complex. The other two government ministries are tasked to oversee domestic trade, co-operatives, urban wellbeing, housing and local government. Multiple functions of the institution may lead to consumer issues being overlooked (Oughton & Lowry, 2000). In this regard, Ardic, Ibrahim and Mylenko ( 2011) stress that the execution of financial consumer protection laws and regulations rely on regulatory and supervisory agencies. The effectiveness of this institutional structure to a large extent determines the success of the implementation of the existing legal framework.